MySQL Connector/Python revealed SQL and NoSQL data storage using MySQL for Python programmers - Krogh, Jesper Wisborg (Apress, 2018)
Move data back and forth between database and application. The must-have knowledge in this book helps programmers learn how to use the official driver, MySQL Connector/Python, by which Python programs communicate with the MySQL database. This book takes you from the initial installation of the connector through basic query execution, then through more advanced topics, error handing, and troubleshooting. The book covers both the traditional API as well as the new X DevAPI. The X DevAPI is part of MySQL 8.0 and is an API that can be used with connectors for several programming languages and is used from the command-line interface known as MySQL Shell. You will learn to use the connector by working through code examples and following a discussion of how the API calls work. By the end of the book, you will be able to use MySQL as the back-end storage for your Python programs, and you'll even have the option of choosing between SQL and NoSQL interfaces. What You'll Learn: Install MySQL Connector/Python Connect to MySQL and configure database access Execute SQL and NoSQL queries from your Python program Trap errors and troubleshoot problems Store data from different languages using MySQL's character set support Work in the X DevAPI that underlies all of MySQL's language connectors.
Includes index. - Online resource; title from PDF title page (Ebsco, viewed August 7, 2018)
Keywords: MySQL (Electronic resource); Python (Computer program language); Python (Langage de programmation); Programming & scripting languages: general; Computer programming; software development; Databases; COMPUTERS; Databases; General